Metasurface-enhanced mid-infrared spectroscopy in the liquid phase. Issue 43 (26th October 2022) - Kharratian, Soheila; Conteduca, Donato; Procacci, Barbara; Shaw, Daniel J.; Hunt, Neil T.; Krauss, Thomas F.
Abstract : A novel surface-enhanced infrared absorption (SEIRA) spectroscopy method exploits the resonance of a dielectric metasurface to provide strong field enhancement at a microscale depth, making it suitable for analysis of dilute liquid samples. Abstract : Vibrational spectroscopy is an important tool in chemical and biological analysis. A key issue when applying vibrational spectroscopy to dilute liquid samples is the inherently low sensitivity caused by short interaction lengths and small extinction coefficients, combined with low target molecule concentrations. Here, we introduce a novel type of surface-enhanced infrared absorption spectroscopy based on the resonance of a dielectric metasurface. We demonstrate that the method is suitable for probing vibrational bands of dilute analytes with a range of spectral linewidths. We observe that the absorption signal is enhanced by 1–2 orders of magnitude and show that this enhancement leads to a lower limit of detection compared to attenuated total reflection (ATR). Overall, the technique provides an important addition to the spectroscopist's toolkit especially for probing dilute samples.